Assessing the Effectiveness of School-Based Health Education on Reproductive Health Knowledge - Puja Mukherjee; Priyha Sharma (Magenta Journal De Healthymedi, 2025)
This study examined the effectiveness of a school-based reproductive health education program in improving adolescents’ reproductive health knowledge and attitudes. A mixed-methods approach was employed, involving 400 high school students divided into intervention and control groups. Quantitative data were collected through pre-test and post-test assessments, while qualitative insights were obtained from student interviews and teacher discussions. The findings revealed a significant increase in reproductive health knowledge among students who participated in the program, particularly in the areas of contraception, sexually transmitted infections, menstrual health, gender equality, and healthy relationships. Participants also reported enhanced self-awareness, confidence, and positive attitudes toward reproductive health issues. However, cultural norms and socio-economic constraints continued to influence the application of knowledge beyond the classroom. The study highlights the effectiveness of comprehensive and interactive school-based reproductive health education in strengthening adolescent health literacy. These findings provide important implications for policymakers, educators, and health practitioners seeking to improve adolescent reproductive health outcomes through curriculum-based educational interventions.